Muscle Cells Recent Advances and Future Perspectives - Valarmathi, Mani T. (IntechOpen, 2020)
The three different types of muscle tissue found in the animal kingdom are cardiac, skeletal, and smooth. The muscle cells are not only complex but also fascinating. In recent years there has been substantial advances in our understanding of muscle cell biology, especially in areas of molecular anatomy, basic physiology, understanding disease mechanisms, and therapeutic targets. Consequently, this book mainly focuses not only on the biology of myocytes, but also on all-encompassing disciplines pertaining to muscle tissue, such as fundamental physiology, molecular mechanisms of diseases, muscle regeneration, etc. for all three types of muscle, namely, skeletal, cardiac, and smooth muscle. As a result, the goal of this book is to consolidate the recent advances in the area of muscle biology/diseases/regeneration covering a broad range of interrelated topics in a timely fashion and to disseminate that knowledge in a lucid way to a greater scientific audience. This book will prove highly useful for students, researchers, and clinicians in muscle cell biology, exercise physiology/science, stem cell biology, developmental biology, cancer biology, pathology, oncology, as well as tissue engineering and regenerative medicine. This quick reference will benefit anyone desiring a thorough knowledge pertaining to recent advances in muscle biology in the context of health and disease.